The risk of transplant failure with HLA mismatch in first adult kidney allografts 2: living donors, summary, guide - Williams, Robert C.; Opelz, Gerhard (Transplantation direct, 2017)
Background Allografts from living donors survive longer than those from deceased donors but the role of HLA mismatching in living kidney donation is still in question. We examined the effect of HLA compatibility on kidney allograft survival from living donors by studying all first adult kidney transplants performed in the United States over 25 years. Methods Using the United Network for Organ Sharing data, we identified first kidney transplants between October 1, 1987, and December 31, 2013. Recipients were classified by their number of HLA mismatches and stratified by donor origin. Cox multivariate regression analyses adjusting for recipient and donor transplant characteristics were performed to determine impact of HLA compatibility on kidney allograft survival for all living donors and for living related and living unrelated subsets. Results There were 66 596 first adult transplants from living donors with 348 960 years of follow-up. We found a linear relationship between HLA mismatch and allograft survival. In adjusted analyses, among all living donors, 1 mismatch conferred a 44% higher risk, whereas 6 mismatches conferred a twofold higher risk of allograft failure. When using 0-mismatched full siblings as a reference, living-donor kidneys reduce the hazard of failure by approximately 34% when compared with deceased donors. Twenty-five years of transplant experience, stratified by donor source, was summarized and presented as a guide for allocation. Conclusions These data reinforce the importance of optimizing HLA matching to further improve survival in first adult kidney allografts in the future, especially in living unrelated donations, when possible.